O poprawną teologicznie ikonę Maryi w kaznodziejstwie - Siwak, Wacław (Studia Pastoralne, 2026)
How a picture of Mary painted by words of a preacher should look like to be theologically correct? Answering this question the author suggests that the picture should be correct in the following contexts: 1) source-wise – taking into consideration basic sources of teaching on Mother of God: Holy Scripture, Tradition of the Church, liturgy, documents of Magisterium Ecclesiae, 2) methodologically-wise – taking into consideration the following issued postulated in the contemporary mariology: showing Mary in correlations to the Persons of the Holy Trinity, the Church and men, where learning about one of the correlates contributes to a deeper understanding of the others, presenting marian content in the context of other theological and humanistic sciences, avoiding maximalism (attributing Mary with prerogatives of Christ, Holy Spirit and the Church) as well as minimalism (diminishing the role of Mary in the history of redemption, undermining the marian dogmas), 3) content-wise – taking into consideration a hierarchy of truths in preaching marian content, hence a proposition: more appreciation for the mystery of the Divine Motherhood, showing a sense of preaching about Mary due to her participation in the Mystery of the Son, underlining close relation of her life with the history of salvation, depicting the Holy Mother as an example to follow.